New drugs in the therapy of multiple myeloma - Jurczyszyn, Artur; Skotnicki, Aleksander (Contemporary Oncology/Współczesna Onkologia, 2007)
Multiple myeloma, a disorder of plasma cells, is the second most common haematological malignancy treated mainly in haematology or oncology clinics. Although treatable, multiple myeloma remains incurable in virtually all cases, with a median survival of 3-4 years. Fortunately for patients with this disease, traditional treatment paradigms have been challenged with the emergence of a number of new therapies entering clinical practice over the last 10 years. In this review, we focus on the use of thalidomide, lenalidomide and bortezomib in the treatment of myeloma. We present the current clinical experience with respect to efficacy and toxicity of these promising new agents and how the incorporation of these drugs with traditional therapies may improve the outcome for patients with multiple myeloma.